Pentingnya Pendidikan Kewirausahaan Ditanamkan Sejak Usia Sekolah Dasar dalam Perspektif Islam - Chintya Pradilla Putri; Zuhrinal M Nawawi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The aim of entrepreneurship education is to develop attitudes, enthusiasm and the ability to create something of value for oneself and others. Creative, innovative, independent, leadership, good money management and never giving up are entrepreneurial attitudes that must be instilled in children from an early age. As followers of the Prophet Muhammad SAW we need to learn from his figure as an entrepreneur. Where in his journey as an entrepreneur, Rasulullah successfully proved that to start a business one does not have to have money first, there are other elements that are more important than that, namely that one must have the right entrepreneurial mentality. The purpose of this article is to analyze the importance of entrepreneurship education instilled from elementary school age in an Islamic perspective. This research uses a qualitative method with a literature-based approach. Qualitative research relies on the collection and analysis of non-numerical data (such as text, video, or audio) to understand concepts, opinions, or results. Entrepreneurship education taught at elementary school level is believed to be able to reduce children's consumption habits, train them to create something of value and give birth to the next generation to create jobs in the future.